2D Monte Carlo simulation of a silicon waveguide-based single-photon avalanche diode for visible wavelengths - Yanikgonul, Salih (2019)
Integrated photonics platforms are crucial to the development and implementation of scalable quantum information and networking schemes, but many such devices still rely on external bulk photodetectors. We report the design and simulation of a waveguide-based single-photon avalanche diode (SPAD) for visible wavelengths. The SPAD consists of a p-n junction implemented in a doped silicon waveguide, which is end-fire coupled to an input silicon nitride waveguide. We developed a 2D Monte Carlo model to simulate the avalanche multiplication process of charge carriers following the absorption of an input photon, and calculated the photon detection efficiency (PDE) and timing jitter of the SPAD. We investigated the SPAD performance at a wavelength of 640 nm and temperature of 243K for different device dimensions and device doping configurations. For our simulated parameters, we obtained a maximum PDE of 0.45 at a reverse bias voltage of ~20 V, and full-width-half-max (FWHM) timing jitter values <8 ps.